Penerapan Metode Pembelajaran Take and Give untuk Meningkatkan Hasil Belajar Kelas IX Mata Pelajaran Akidah Akhlak di MTs Hidayatul Mubtadiin Lampung selatan - Erni Ardiyanti; Mujiatun Mujiatun; Ami Latifah (Journal on Education, 2023)
This study aims to evaluate the application of the Take and Give learning method in improving learning outcomes in the Akidah Akhlak subject at MTs Hidayatul Mubtadiin Jati Agung. The Take and Give method is an interactive approach that involves teachers and students in the learning process by sharing knowledge. This research uses descriptive qualitative, research data obtained from observation, interviews and documentation. The results showed that the application of the Take and Give learning method significantly increased student learning outcomes in the Aqidah Akhlak subject. There is a significant increase in understanding the concept, student participation, and active involvement in the learning process. Evidenced by the increase in learning outcomes, namely before the Akidah Akhlak subject teacher applied this method 6 students received a complete score and after the teacher used this method 17 students were declared complete. These findings indicate that the Take and Give method can be used effectively to improve learning outcomes in the Aqidah Akhlak subject at MTs Hidayatul Mubtadiin Jati Agung.